STUDI IDENTIFIKASI KEBERADAAN Escherichia coli PADA AIR CUCIAN DAN MAKANAN KETOPRAK DI KAWASAN KAMPUS UNDIP TEMBALANG - Chintya Pangestika; Yusniar Hanani Darundiati; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
The dishwater used by ketoprak traders in the area of UNDIP campus Tembalang is not qualified physically. In this situation, it will have an impact on the quality of the food produced. This study aimed to identify the existence of Escherichia coli in dishwater used to wash utensils and the ketoprak food. The type of this study is observational with cross sectional design. The population in this research is 11 dishwater and 11 ketoprak food. The sample in this study used the total population. The analysis applied cross tabulation. The sanitary conditions of the dishwater is not good and positive existence of E.coli in dishwater by 8 as many as (88,9%). Washing techniques that are less good and positive existence of E.coli in dishwater as many as 2 traders (100%). The sanitary conditions of the dishwater is not good and positive existence of E.coli in ketoprak food as many as 9 traders (100%). Washing techniques that are less good and positive existence of E.coli in ketoprak as many as 2 traders (100%).The sanitary conditions of cutlery were poor and positive existence of E. coli in ketoprak food as many as 9 traders (90%). Storage of food which has been treated poorly and positive existence of E. coli in ketoprak food as many as 7 traders (100%). Personal hygiene handlers are less and positive the existence of E. coli in ketoprak food as many as 6 traders (100%). The conclusion of this study is the quality of the dishwater and ketoprak food in the area of UNDIP Campus Tembalang is not eligible.